The Health Behaviours of Students from Selected Countries-A Comparative Study - Małgorzata Lesińska-Sawicka; Ewa Pisarek; Małgorzata Nagórska (MDPI AG, 2021)
Health behaviour defined as any behaviour that may affect an individual's physical and mental health or any behaviour that an individual believes may affect their physical health. It is strongly related to their culture and plays a major role in shaping all health and illness-related behaviour. The purpose of the study was to compare and evaluate the lifestyles of students from multiple countries. The proposed work will determine the deficits in health behaviors undertaken by students. The survey was carried out from December 2016 to March 2017 comprising 532 students from Poland, Hungary, Turkey, and Greece. The sample was selected using the snowball method: a link to the online questionnaire was sent to students from the given countries via the Internet. For some participants, who did not have access to the online questionnaire, printed copies were used instead. As a method was used a diagnostic survey and the survey technique. The opinions of students were measured using the 5-level Likert scale with a neutral option. Students undertook health-promoting activities, but also list behaviours that did not contribute to strengthening their health. Students were shown to have the greatest problems with physical health behaviours and health prevention. There were noticeable differences in the lifestyle of students from different countries.